An Accentuated Technique Aimed at Fostering High-Speed Qualities in Children 12-14 Years Old Engaged in Taekwondo (Eurasian Journal of Learning and Academic Teaching, 2022)
The article outlines an accentuated methodology aimed at educating speed capabilities in young taekwondo fighters. The author's methods were experimentally tested on the basis of the developed complexes of physical exercises